R. El̔azar son of R. Šim̔on the thief catcher (bB. Metz. 83a–84a) - Hevroni, Ido (Journal of Jewish studies, 2023)
The article analyses the first half of the story cycle about R. El̔azar son of R. Šim̔on with regard to its literary and redactional aspects and its web of contexts. The cycle’s chiastic structure is identified, as well as its ‘symphonic’ character: motifs appearing for the first time in the Mishnah are repeated in different variations throughout the sugya, creating a dialogue among its various units. The article concludes that, despite R. El̔azar’s irregular conduct, this is not a tale of repentance. The stories instead depict the changes in R. El̔azar’s attitude towards ‘natural law’. In the opening story R. El̔azar seeks divine order through observing the outside world; in the last story he arrives at the conclusion that his body is the tool through which divine order can be recognized.